1995
DOI: 10.3133/wri944253
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of ground water in the Gallup, Dakota, and Morrison aquifers, San Juan Basin, New Mexico

Abstract: Ground water was sampled from wells completed in the Gallup, Dakota, and Morrison aquifers in the San Juan Basin, New Mexico, to examine controls on solute concentrations. Samples were collected from 38 wells primarily from the Morrison aquifer (25 wells) in the northwestern part of the basin. A series of samples was collected along groundwater flow paths; dissolved constituents varied horizontally and vertically. The understanding of the flow system changed as a result of the geochemical analyses. The concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The most prevalent of these constituents were arsenic, grossalpha radioactivity, manganese, and combined radium . Previous studies in the Colorado Plateaus aquifers have also found elevated arsenic concentrations (Welch and others, 1988;Dam, 1995). The distribution of moderate and high concentrations of arsenic and manganese occurred primarily in the southern half of the Colorado Plateaus aquifers, in southern Utah and northern Arizona and New Mexico, whereas elevated concentrations of radioactive constituents occurred throughout the aquifer.…”
Section: Benchmarks For Evaluating Groundwater Qualitymentioning
confidence: 64%
“…The most prevalent of these constituents were arsenic, grossalpha radioactivity, manganese, and combined radium . Previous studies in the Colorado Plateaus aquifers have also found elevated arsenic concentrations (Welch and others, 1988;Dam, 1995). The distribution of moderate and high concentrations of arsenic and manganese occurred primarily in the southern half of the Colorado Plateaus aquifers, in southern Utah and northern Arizona and New Mexico, whereas elevated concentrations of radioactive constituents occurred throughout the aquifer.…”
Section: Benchmarks For Evaluating Groundwater Qualitymentioning
confidence: 64%